Bradykinesia induced by frequency-specific pallidal stimulation in patients with cervical and segmental dystonia - Hübl, Julius; Blahak, Christian (Parkinsonism & related disorders, 2015)
Introduction: Pallidal deep brain stimulation (DBS) is an effective treatment for patients with primary dystonia leading to a substantial reduction of symptom severity. However, stimulation induced side effects such as bradykinesia have also been reported recently. The influence of stimulation parameters on such side effects have not yet been systemically assessed in these patients. Methods: Here we tested the effect of stimulation frequency and duration of stimulation period on hand motor function in 22 patients with primary cervical and segmental dystonia using an unimanual tapping task. Patients performed the task at 4 different stimulation frequencies (0 Hz = OFF stimulation, 20, 50 and ≥130 Hz = high frequency stimulation) after either an SHORT (5 min, N = 16) or a LONG (60 min, N = 6) stimulation period (i.e. changing of DBS-frequency). The change of overall mobility under HFS compared to the preoperative state was assessed with a 5-point Likert-scale. Tapping performance was analysed using a repeated measures ANOVA with the main factor ‘FREQUENCY’. Tapping performance at HFS and changes in general mobility were correlated using Spearman's Rho. Results: We found a frequency specific modulation of hand motor function: HFS led to deterioration and 20 Hz stimulation to improvement of tapping rate. The effects were predominant in the ‘LONG’ group suggesting a significant contribution of stimulation duration. Conclusions: This is important to consider during DBS-programming and evaluation of potential side effects. Furthermore, the impairment in hand motor function under HFS was mirrored by the patients' observation of a deterioration of general mobility.